Pengaruh Biaya Produksi, Biaya Administrasi Umum, dan Biaya Pemasaran Terhadap Laba Pada Perusahaan Food and Beverages Yang Terdaftar Di Bursa Efek Indonesia - Broto, Andri Hasmoro Kusumo; Sripeni, Rusbiyanti; Permatasari, Retno Windu (JURNAL EKOMAKS : Jurnal Manajemen, Ekonomi Kreatif dan Bisnis, 2018)
AbstractThis study aims to: (a) determine the partial effect of production costs on profits in food and beverages company listed on the Indonesia Stock Exchange. (b) To determine the effect of partial general administrative costs on profits in listed food and beverages company On the Indonesia Stock Exchange. (c) To determine the effect of partial marketing costs on profits in food and beverages company listed on the Indonesia Stock Exchange. (d) To determine the simultaneous effect of production costs, general administrative costs, and costs income to the food and beverages company listed in the Indonesia Stock Exchange. The population in this study is a food and beverages company listed on the Indonesia Stock Exchange in 2017. Data collection techniques use quarterly financial statements. Sampling purposive sampling technique. Data analysis techniques use multiple linear regression and hypothesis test (t test and F test). The results show: (a) there is a partial significant negative effect on production costs on profits in the food and beverages company listed on the Indonesia Stock Exchange. (b) There is a partial significant negative effect on general administration costs on profits in the food and beverages company listed on the Indonesia Stock Exchange. (c) There is a partial significant negative effect on marketing costs on profits in the food and beverages company listed on the Indonesia Stock Exchange. (d) There is a significant negative effect simultaneously production costs, general administrative costs, and marketing costs to earnings at food and beverages company listed in Indonesia Stock Exchange.Â Keywords: Production Costs, General Administrative Costs, Marketing Costs, Profit